Digital Twin for Climate Resilience: Transforming Smart Cities for a Sustainable Future - E. Ali; E. Ali; A. Mansour; A. Mansour; E. Mohammed Abdelkader; N. Elshaboury; T. Zayed (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The urgency of climate change demands innovative solutions that transcend traditional mitigation and adaptation strategies. In this context, Digital Twins (DTs) have emerged as a transformative tool for integrating real-time data, advanced simulation, and predictive analytics across diverse domains. This paper presents a comprehensive review of DT applications that bolster climate resilience, emphasizing how the technology can drive decarbonization, enhance resource efficiency, and mitigate urban heat island effects. We categorize DT implementations into three spatial scales—small-scale assets, city-level systems, and global or Earth-level networks—illustrating the versatility and scalability of DT-driven interventions. Subsequently, we delve into key sectoral applications, including green building practices, climate-responsive construction, and precision agriculture, illustrating how DTs can optimize operational processes and reduce greenhouse gas emissions. By synthesizing findings from leading studies and real-world case examples, we highlight both the current achievements and the challenges—such as data standardization, computational demands, and stakeholder engagement—that hamper wider DT adoption. We argue that addressing these hurdles through cross-disciplinary collaboration, regulatory support, and technological innovation is critical for fully leveraging DTs’ potential in climate resilience. Overall, this paper underscores DTs as a promising catalyst for transformative change, offering data-driven insights that guide policy and practice toward a more sustainable, equitable, and climate-resilient future.